Development of grid-tie home electricity supply system (GHESS) using solar energy - See, Kok Leng. (2014)
The title of this dissertation is Development of Grid-Tie Home Electricity Supply System (GHESS) Using Solar Energy. This report covers the concept, design and implementation details of a GRESS using solar photovoltaic energy as the main source of energy. A simulation model was constructed and simulated using the Matlab® Simulink software and a functional prototype was physically built and tested. The system performance data of the functional prototype was collected for analysis and verification with the design and simulated data.